2019
DOI: 10.3389/fendo.2019.00334
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Refractory Pituitary Adenomas

Abstract: Refractory pituitary adenomas (PAs) are defined as aggressive-invasive PAs characterized by a high Ki-67 index, rapid growth, frequent recurrence, and resistance to conventional treatments. It is notoriously difficult to manage refractory PAs because the efficacy of current therapeutic options is limited. The purpose of this review is to address currently employed and promising therapeutic strategies for the treatment of refractory PAs. Except for prolactinomas, neurosurgery is the first-line option, but most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 110 publications
0
29
0
1
Order By: Relevance
“…Although the understanding of the molecular pathogenesis of PCs has progressed rapidly, the early identification of PC is difficult until the presence of metastatic lesions. Refractory PAs lie between benign adenomas and true malignant PC and are defined as aggressive-invasive PAs characterized by a high Ki-67 index, rapid growth, frequent recurrence, and resistance to conventional treatments, including temozolomide (TMZ) (10,11). Therefore, both refractory PAs and PCs are very difficult to manage due to the lack of effective treatment, and they are associated with increased morbidity and mortality (12).…”
Section: Introductionmentioning
confidence: 99%
“…Although the understanding of the molecular pathogenesis of PCs has progressed rapidly, the early identification of PC is difficult until the presence of metastatic lesions. Refractory PAs lie between benign adenomas and true malignant PC and are defined as aggressive-invasive PAs characterized by a high Ki-67 index, rapid growth, frequent recurrence, and resistance to conventional treatments, including temozolomide (TMZ) (10,11). Therefore, both refractory PAs and PCs are very difficult to manage due to the lack of effective treatment, and they are associated with increased morbidity and mortality (12).…”
Section: Introductionmentioning
confidence: 99%
“…Other transcriptomic studies that could be compared to our results are reports that have assessed the invasiveness of the PitNETs. The invasiveness could also be related to increased cell growth, and in PitNETs, it has been demonstrated that resistance to SSA is accompanied with reduced tumor shrinkage ( 51 ). In the transcriptome studies comparing invasive and non-invasive PitNETs, there are various candidates identified that are related to cell proliferation, growth, apoptosis pathways, but still rarely these candidates overlap between the studies ( 49 , 50 , 52 58 ) ( Supplementary Material Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This definition was derived by summarizing the clinical characteristics and pathological findings of a group of patients with refractory PAs from Peking Union Medical College Hospital (PUMCH). The diagnostic criteria for refractory PAs were also proposed as follows: 1) tumor infiltration of adjacent structures according to radiological results or intraoperative findings; 2) Ki-67 index greater than 3%, and growth velocity greater than 2% per month; 3) failure of current treatments to control tumor growth and/or hormonal hypersecretion; and 4) tumor recurrence within 6 months after surgery ( 37 ). Although the term “refractory” has caused some controversy ( 38 ), it does provide a more accurate definition and more objective diagnostic criteria for these invasive-aggressive PAs.…”
Section: Controversies In the Classification And Definition Of Pituitmentioning
confidence: 99%